SharePoint 2007 how-to - Sagi, Ishai (Sams, 2009)
SharePoint® 2007 How-To Ishai Sagi Real Solutions for SharePoint Users SharePoint 2007 How-To delivers quick, to-the-point answers to common problems and tasks in SharePoint 2007. You'll find answers to the most common end-user tasks, as well as some of the more complex problems and tasks faced by content and site managers. From the basics of navigating a site, to more complex tasks such as customizing a site and managing site security, SharePoint 2007 How-To is a focused resource that provides access to all the answers you need--now! Fast, Accurate, and Easy to Use! . Discover all the core SharePoint components and their practical uses and applications . Learn the essentials for navigating a SharePoint site . Find fresh ideas for working with the various SharePoint file formats . Perform detailed searches within SharePoint . Manage personal sites . Create organized lists and document libraries that are easy to navigate . Modify and customize list views by using filtering, grouping, and sorting . Control user access by managing permissions for lists, libraries, files, and other components . Implement and track custom workflows within SharePoint . Create subsites for enhanced content management . Customize the look and feel of a site using custom settings, themes, and content types . Manage site permissions and settings for a more secure environment Ishai Sagi is a SharePoint expert who has been working in Microsoft SharePoint since its initial release in 2001. Currently, Ishai is a SharePoint developer and solutions architect in Canberra, Australia. He spends his spare time leading the Canberra SharePoint user group. Since the Microsoft SharePoint launch in 2001, Ishai has trained numerous end users, administrators, and developers in using Microsoft SharePoint or developing solutions for the platform. He has spoken at Microsoft conferences in countries around the world, including Spain, Israel, and Australia. Ishai was the recipient of the Microsoft Most Valuable Professional (MVP) award for SharePoint in 2007, 2008, and 2009. Ishai also is the author of a popular SharePoint blog for developers at http://www.sharepoint-tips.com and manages the Canberra SharePoint User Group website at http://www.sharepointusers.org.au/Canberra/default.aspx. Category: Microsoft Servers/SharePoint User Level: Beginner-Intermediate.